How do you solve -3/(4x) + 3/8 = 27/32?

2 Answers
Mar 24, 2018

x = -1.6

Explanation:

-3/(4x) + 3/8 = 27/32
-3/(4x) = 27/32- 3/8
-3/(4x) = 27/32 - 12/32
-3/(4x) = 15/32
By cross-multiplication:
4x*15 = -3*32
60x = -96
x = -96/60
x = -1.6

Mar 24, 2018

x=-8/5

Explanation:

Before we do anything, we need to get a common denominator of 32.

-3/4x=-24/32x (multiplying top and bottom by 8)

3/8=12/32 (multiplying top and bottom by 4)

27/32 will stay the same

Thus, we have

-24/32x+12/32=27/32

We can subtract 12/32 from both sides to get

-24/32x=15/32

We can cross multiply to get:

x=(-24*cancel32)/(cancel32*15)

Since the 32s will cancel, we're left with:

(-24)/(15)

Which can be simplified to x=-8/5